2017
DOI: 10.1016/j.molcel.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Vps34 Kinase Domain Dynamics Regulate the Autophagic PI 3-Kinase Complex

Abstract: Summary The class III phosphatidylinositol 3-kinase complex I (PI3KC3-C1) is required for the initiation of essentially all macroautophagic processes. PI3KC3-C1 consists of the lipid kinase catalytic subunit VPS34, the VPS15 scaffold, and the regulatory BECN1 and ATG14 subunits. The VPS34 catalytic domain and BECN1:ATG14 subcomplex do not touch, and it is unclear how allosteric signals are transmitted to VPS34. We used EM and cross-linking mass spectrometry to dissect five conformational substates of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 55 publications
3
83
0
Order By: Relevance
“…Mechanistic work indicates that the SAC1 domain of Synj1 is needed to dephosphorylate PI(3)P, and likely also PI(3,5)P 2 , on synaptic The EMBO Journal 37: e98960 | 2018 autophagosomal membranes (Vanhauwaert et al, 2017). These phosphoinositides, produced by Vps34 and Fab1, respectively, are critically required during the initial steps, and likely in the maturation steps, of autophagy (Rusten et al, 2007;Juhász et al, 2008;Thoresen et al, 2010;Stjepanovic et al, 2017). However, as the autophagosome matures, these phosphoinositides need to be dephosphorylated to lower the affinity of specific autophagic factors such as Atg18a/WIPI2, allowing autophagosome formation to move forward.…”
Section: Synj1mentioning
confidence: 99%
“…Mechanistic work indicates that the SAC1 domain of Synj1 is needed to dephosphorylate PI(3)P, and likely also PI(3,5)P 2 , on synaptic The EMBO Journal 37: e98960 | 2018 autophagosomal membranes (Vanhauwaert et al, 2017). These phosphoinositides, produced by Vps34 and Fab1, respectively, are critically required during the initial steps, and likely in the maturation steps, of autophagy (Rusten et al, 2007;Juhász et al, 2008;Thoresen et al, 2010;Stjepanovic et al, 2017). However, as the autophagosome matures, these phosphoinositides need to be dephosphorylated to lower the affinity of specific autophagic factors such as Atg18a/WIPI2, allowing autophagosome formation to move forward.…”
Section: Synj1mentioning
confidence: 99%
“…Recruitment of a complex containing Vps34 is an important early step in autophagy and phagocytosis, although complexes of different compositions are associated with each. In the canonical autophagy pathway, cellular stress activates the ULK1 complex, which in turn activates the PI3KC3 complex I, containing the scaffold protein Vps15, Atg14, Beclin 1 and the type III phosphoinositide 3-kinase, Vps34 (Stjepanovic et al, 2017); this activation leads to extension of a double-membrane phagophore enriched in PI(3)P (Axe et al, 2008;Hayashi-Nishino et al, 2009;Itakura and…”
Section: Introductionmentioning
confidence: 99%
“…The kinase domain of VPS15 keeps basal activity low by restricting the activation loop of VPS34 (12). Our laboratory previously found that the VPS34 kinase domain is highly dynamic (11,27). We found that "leashing" the VPS34 kinase domain to the VPS15 kinase domain with a 12-residue linker blocked even basal kinase activity (Stjepanovic et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
“…Our laboratory previously found that the VPS34 kinase domain is highly dynamic (11,27). We found that "leashing" the VPS34 kinase domain to the VPS15 kinase domain with a 12-residue linker blocked even basal kinase activity (Stjepanovic et al, 2017). This showed that a substantial structural change relative to the published PI3KC3-C2 conformation was essential for any activity, yet the precise nature of the structural change was not clear.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation